Contextual barriers to PrEP uptake and continuation among young Black gay and bisexual men who have sex with men living in the South - Maira Sohail; Andrew O. Westfall; Ashleigh Chiedo; Bernadette Johnson; K. Rivet Amico; Patrick S. Sullivan; Jeanne Marrazzo; Janet M. Turan; Michael J. Mugavero; Latesha Elopre (PLoS ONE, 2025)
Young, Black Gay, and Bisexual men who have sex with men (YBGBM) are disproportionately impacted by HIV, especially in Southern United States. We conducted a cross-sectional survey (Feb19-Mar20). Eligibility criteria were self-reported age 16–29 years, HIV-negative, Black race, and cis-gender male. We assessed associations between demographics, religiosity, intersectional stigma, and pre-exposure prophylaxis (PrEP) use (never, previous or current) among YBGBM in Alabama. Univariate and multivariable multinomial logistic regression models were fit with factors selected a priori, guided by a conceptual framework including individual-, interpersonal- and structural-level barriers to PrEP. 305 participants completed surveys (median age 24, 75% employed, 32% lacked personal transportation, and 41% reported annual incomes < $15,000). Compared to never PrEP use (n = 219), factors associated with current PrEP use (n = 51) included: ≥ college degree [AOR (95% CI): 5.48 (2.05, 14.62)], friends’ social support [AOR (95% CI): 1.33 (1.00, 1.52)], perceived HIV risk [AOR (95% CI): 1.27 (1.14, 1.42)], and PrEP knowledge [AOR (95% CI): 1.42 (1.23, 1.65)] AND factors associated with previous PrEP use (n = 35) included: depression [AOR (95% CI): 3.08 (1.34, 7.09)], condom use less than all the time [AOR (95% CI): 11.98 (1.52, 94.41)], intrinsic religiosity [AOR (95% CI): 0.77 (0.68, 0.88)], stable housing [AOR (95% CI): 0.30 (0.11, 0.81)], perceived sexual stigma [AOR (95% CI): 0.84 (0.75, 0.94)], and perceived HIV risk [AOR (95% CI): 1.18 (1.05, 1.33)]. YBGBM face distinct challenges with engagement in HIV prevention services and further investigation is needed to understand individual, interpersonal as well as structural-level factors that may mediate the ability to utilize PrEP services. Tailored multilevel strategies are urgently needed to improve PrEP uptake and persistence in YBGBM.